"UFV-4", variedade de soja para o Cerrado do Brasil Central - Sediyama, Tuneo; Sediyama, Carlos S; Athow, Kirk L; S Reis , Múcio; Pereira , Messias G; Martins , Oswaldir; Dutra, José H; E Arantes , Neylson (Revista Ceres, 2025)
“UFV-4" is a high yielding soybean variety adapted to soil of medium fertility between 16o and 23o South Latitude. This variety originated from a cross between IAC-2’ and ‘Mineira’ varieties. The segregating population was treated by an adaptation of the Modified Pedigree Method which consisted of using a single pod descendent per plant instead of the single seed descendent per plant.